2014
DOI: 10.1186/1556-276x-9-682
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and density control of GaN nanodots on Si (111) by droplet epitaxy using plasma-assisted molecular beam epitaxy

Abstract: In this report, self-organized GaN nanodots have been grown on Si (111) by droplet epitaxy method, and their density can be controlled from 1.1 × 1010 to 1.1 × 1011 cm-2 by various growth parameters, such as substrate temperatures for Ga droplet formation, the pre-nitridation treatment of Si substrate, the nitridation duration for GaN crystallization, and in situ annealing after GaN formation. Based on the characterization of in situ RHEED, we can observe the surface condition of Si and the formation of GaN na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
(20 reference statements)
0
8
1
Order By: Relevance
“…On the other hand, visible planar defects can be caused by polarity inversion at domain boundaries. [12], [13] and according to our studies there is no direct correlation between surface density of the nanoislands of the seeding layer and density of the synthesized GaN nanoparticles. But despite that fact, it has been found that the effective thickness of the seeding layer significantly affects further GaN growth.…”
Section: Structure and Morphology Of Y-shaped Gan Nanoparticles (Gan contrasting
confidence: 53%
“…On the other hand, visible planar defects can be caused by polarity inversion at domain boundaries. [12], [13] and according to our studies there is no direct correlation between surface density of the nanoislands of the seeding layer and density of the synthesized GaN nanoparticles. But despite that fact, it has been found that the effective thickness of the seeding layer significantly affects further GaN growth.…”
Section: Structure and Morphology Of Y-shaped Gan Nanoparticles (Gan contrasting
confidence: 53%
“…GaN nanodots grown by the method of droplet epitaxy were carried out in our ULVAC MBE system with a radio frequency (RF) nitrogen plasma source [19]. Two inch Si (111) wafers were cleaned using acetone to remove organic impurities and using 10% HF solution to remove the native oxide.…”
Section: Methodsmentioning
confidence: 99%
“…Density of GaN nanodots can be controlled by the growth parameters. Metastable zinc-blende structure can be performed in the GaN nanodots on sapphires by droplet epitaxy [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Among these nitride-based materials, gallium nitride (GaN) nanocrystals (NCs) with a direct wide band gap (3.34 eV) extensively have been studied for the use of next generation devices, such as photovoltaic, solid-state quantum computation, and single-photon sources [4][5][6][7] . To achieve GaN nanostructures on a substrate, various techniques such as self-assembly growth, vapor-liquid-solid (VLS) process using molecular beam epitaxy (MBE), and metal organic chemical vapor deposition (MOCVD) have been widely used so far [8][9][10] . For example, Zhang et al reported the formation of GaN NCs via thermal decomposition by MOCVD 11 .…”
mentioning
confidence: 99%
“…For example, Zhang et al reported the formation of GaN NCs via thermal decomposition by MOCVD 11 . Additionally, GaN nanodots were grown via Ga droplet epitaxy using pretreatment and post-annealing procedure and converted from Ga 2 O 3 using combustion process 10,12,13 . These methods, however, can exhibit the limited introduction of GaN nanostructures into the desirable applications, because of the complicated growth process and low throughput.…”
mentioning
confidence: 99%